Zastosowanie instrumentów zarządzania finansami osobistymi w polskich gospodarstwach domowych - Musiał, Marta (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2015)
One of the most important elements of managing personal finances is collectionof data needed for the analysis of household’s financial situation. The mostpopular personal finance management tools include financial statements (balancesheets and cash flows) and household budget. The purpose of this article isto determine how Polish households use the basic personal finances management tools. The article will characterize the tools and present the results of primarystudies concerning the use of these tools by Polish households.